Psychological Contracts and Employment Relationships (A Review Paper) - Arshad, Faisal; Mohiuddin, Zaeema Asrar; Ahmed, Farooq; Zaidi, Syed Shahid Zaheer (Archives of Business Research, 2017)
A psychological contract comprises of a personal viewpoint about mutual commitments in employment relationships. Unlike a traditional service contract, the psychological contract remains unspoken in the employment relationship between employer and the employees. Employees anticipate, for example, working in a secure and clean environment; to work with qualified and regimented co-workers and to be appreciated for their good work, free from harassment etc. Employers, on the contrary, expect staff to be careful and dedicated; to be trustworthy; and to maintain or enhance the organizational image etc. This shady nature and often conflicting nature of psychological contract can often harm the health of employment relationship.This paper explores the nature of psychological contracts and their significance within the domain of employment relationships. The paper first reviews the general theory of psychological contract, its types and factors governing them. Next, a theoretical examining the research contributions of scholars who have contributed to the literature is being carried out. Finally, the paper thoroughly and critically analyzes the effects of breach or non-conformity of psychological contracts.Psychological contract plays a key role in manipulating workers job related commitment. It must be highlighted that effective observation, agreement and execution of psychological contracts could add to increased levels of workers commitment.Considering the literature studied, it becomes extremely important for the management to be responsive of, and to some degree control, the psychological contracts that the employees may hold. Offering the aggrieved employees a practical psychological contract diminishes the probability that the workforce will see the agreement as void. Increased levels of work independence is also found to reduce incidents of psychological contract breaches.